Chronic Inflammation Links Cancer and Parkinson’s Disease - Li, Zhiming; Zheng, Zaozao; Ruan, Jun; Li, Zhi; Tzeng, Chi-Meng (Frontiers in Aging Neuroscience, 2016)
An increasing number of genetic studies suggest that the pathogenesis of Parkinson’s disease (PD) and cancer share common genes, pathways, and mechanisms. Despite a disruption in a wide range of similar biological processes, the end result is very different: uncontrolled proliferation and early neurodegeneration. Thus, the links between the molecular mechanisms that cause PD and cancer remain to be elucidated. We propose that chronic inflammation in neurons and tumors contributes to a microenvironment that favors the accumulation of DNA mutations and facilitates disease formation. This article appraises the key role of microglia, establishes the genetic role of COX2 and CARD15 in PD and cancer, and discusses prevention and treatment with this new perspective in mind. We examine the evidence that chronic inflammation is an important link between cancer and PD.